2013
DOI: 10.1016/j.pain.2013.06.045
|View full text |Cite
|
Sign up to set email alerts
|

Longstanding neuropathic pain after spinal cord injury is refractory to transcranial direct current stimulation: A randomized controlled trial

Abstract: Neuropathic pain remains one of the most difficult consequences of spinal cord injury (SCI) to manage. It is a major cause of suffering and adds to the physical, emotional, and societal impact of the injury. Despite the use of the best available treatments, two thirds of people experiencing neuropathic pain after SCI do not achieve satisfactory pain relief. This study was undertaken in response to a recent clinical trial reporting short-term, clinically significant reductions in neuropathic SCI pain with prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
2
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(104 citation statements)
references
References 29 publications
2
99
2
1
Order By: Relevance
“…Contrasting with these findings, other tDCS trials indicate there were no significant differences in pain reduction following active and sham stimulation [25]. In addition, nothing is known about the effects of tDCS on quality of life in people with sublesional neuropathic pain due to SCI.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…Contrasting with these findings, other tDCS trials indicate there were no significant differences in pain reduction following active and sham stimulation [25]. In addition, nothing is known about the effects of tDCS on quality of life in people with sublesional neuropathic pain due to SCI.…”
Section: Introductionmentioning
confidence: 65%
“…One of them investigated the effect of 5 sessions of tDCS on pain level in a small sample of patients with SCI (n = 10); no difference between active and sham tDCS was observed [25]. The authors explained that lack of effects is likely due to refractoriness of pain and duration of disease since most of the patients enrolled had injury durations of 10 or more years.…”
Section: Delayed Tdcs Effects On Pain Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 A fourth study did not find a significant difference between tDCS and sham control. 34 A prospective-controlled trial that found a significant reduction in pain intensity, compared with sham control, was upgraded because of small confidence intervals and the inclusion of an intention-to-treat analysis. 35 A meta-analysis of the five studies found a positive effect for transcranial direct current stimulation on pain intensity.…”
Section: Third-line Therapy Recommendation 26mentioning
confidence: 99%
“…These included two double-blinded randomized controlled trials (RCTs), 12,19 two doubleblinded crossover RCTs, 20,21 and one prospective controlled trial. 22 The methodological quality was excellent for the four RCTs, 12,[19][20][21] whereas the prospective controlled trial 22 was fair in quality (Table 1). …”
Section: Study Selection and Qualitymentioning
confidence: 99%